Auditory perception bias in speech imitation - Postma-Nilsenová, Marie; Postma, Eric (Frontiers in Psychology, 2013)
In an experimental study, we explored the role of auditory perception bias in vocal pitch imitation. In line with neuroanatomical differences in the lateral Heschl's gyrus, some listeners show an auditory perception bias for the sound as a whole which facilitates their perception of the fundamental frequency (the primary acoustic correlate of pitch). Other listeners focus on the harmonic constituents of the complex sound signal which may hamper the perception of the fundamental. These two listener types are referred to as fundamental and spectral listeners, respectively. We hypothesized that the individual differences in speakers' capacity to imitate F0 found in earlier studies, may at least partly be due to the capacity to extract information about F0 from the speech signal. Participants' auditory perception bias was determined with a psychoacoustic perceptual test involving a missing fundamental. Subsequently, speech data were collected in a shadowing task with two conditions, one with a full speech signal and one with high-pass filtered speech above 300 Hz. The results showed that perception bias towards fundamental frequency was related to the degree of F0 imitation. The effect was stronger in the condition with high-pass filtered speech. The experimental outcomes suggest advantages for fundamental listeners in communicative situations where F0 imitation is used as a behavioral cue. Future research needs to determine to what extent auditory perception bias may be related to other individual properties known to improve imitation, such as phonetic talent.